Innovation, firm size distribution, and gains from trade - CHEN, Yi-Fan (Institutional Knowledge at Singapore Management University, 2018)
We study a trade model with monopolistic competition a la Melitz (2003) that is standard except that firm heterogeneity is endogenously determined by firms innovating to enhance their productivities. We show that the equilibrium productivity and firm-size distributions exhibit power-law tails under rather general conditions on demand and technology. In particular, the emergence of the power laws is essentially independent of the underlying primitive heterogeneity among firms. We investigate the model’s welfare implications, and conduct a quantitative analysis of welfare gains from trade. We find that, conditional on the same trade elasticity and values of the common parameters, our model yields 40% higher welfare gains from trade than a standard model with exogenously given productivity distribution.